3D Head Orientation Estimation and Expression Influence Minimization using Characteristic Points of Face - Dervinis, D.; Daunys, G.; Ramanauskas, N. (Elektronika ir Elektrotechnika, 2008)
The method of minimization face expression influence for evaluation of head orientation in space is proposed and investigated. In our previous works 18 characteristic face points were selected for the head orientation evaluation. It is difficult to track all 18 points in real time. It was found by way of mathematical simulation that number of points 7 is optimal number for head orientation tracking. The points were selected at the face places which obtain minimal changes because of face expression. Mathematical simulation helped to establish that errors for head rotations could reach value 13 degrees (for surprised expression), and mean error is about 6-8 degrees. After correction of face specific points coordinates by mean value of change caused by face expression the errors were reduced until range 0.1-0.3 degrees. Intervals of possible errors for every expression and some head orientation angles were calculated. The method was tested using CMU PIE database of face images. The obtained interval for head orientation angles errors is 1.5-2.8. The correspondence of 78-90% was obtained between results of experimental errors and results of mathematical simulation. Ill. 6, bibl. 7 (in English; summaries in English, Russian and Lithuanian).